Financialization of Water: Conceptual Analysis of the California Water Crisis - Orobello, Christian; Cirella, Giuseppe T. (Frontiers in Environmental Science, 2021)
Water is a rapidly shrinking commodity. As we continue to use water for industry, farming, and sustaining our own lives, we must realize its intrinsic value. In December of 2020, water was given a new value as a future on a commodities market. This paper aims to discuss the practical, ethical, and financial considerations of trading water in this manner. A thorough conceptual analysis of the literature and research from 2009 to 2020 related to commodities and their history was performed, and a more contemporary review of water policy and pricing. The goal is to develop a mixed solution that gives value to water without allowing it to be exploited to the detriment of the poor; water must be accessible and affordable if it is to be managed ethically. Approaching water as a high-value resource might create a market that makes it unobtainable for most of us; however, with a system that controls pricing, creates standards, and simultaneously works to increase the supply of water, we may be able to create a “market.” Our critique of the research and available solutions indicates rising water prices and mostly regressive policies. As a result, market controls need to be implemented to control pricing while ensuring water availability for all.